2005
DOI: 10.1128/jvi.79.14.8812-8827.2005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Immunogenicity of a Disulfide-Stabilized, Cleaved, Trimeric Form of the Envelope Glycoprotein Complex of Human Immunodeficiency Virus Type 1

Abstract: The human immunodeficiency virus type 1 (HIV-1) envelope glycoprotein (Env) complex comprises three gp120 exterior glycoproteins each noncovalently linked to a gp41 transmembrane glycoprotein. Monomeric gp120 proteins can elicit antibodies capable of neutralizing atypically sensitive test viruses in vitro, but these antibodies are ineffective against representative primary isolates and the gp120 vaccines failed to provide protection against HIV-1 transmission in vivo. Alternative approaches to raising neutrali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
112
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(117 citation statements)
references
References 79 publications
(111 reference statements)
5
112
0
Order By: Relevance
“…Our preclinical study results also indicated that this combination vaccination approach, but not recombinant protein alone, was effective in eliciting NAbs against primary HIV isolates [19], a finding that has been confirmed subsequently by other independent studies [20][21][22][23][24][25][26]. Furthermore, when polyvalent primary Env antigen formulations were used, the DNA primeprotein boost approach was more effective than the monovalent primary Env antigen in eliciting rabbit NAbs against a wide range of selected primary viral isolates across subtypes A, B, C, D and E [27].…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our preclinical study results also indicated that this combination vaccination approach, but not recombinant protein alone, was effective in eliciting NAbs against primary HIV isolates [19], a finding that has been confirmed subsequently by other independent studies [20][21][22][23][24][25][26]. Furthermore, when polyvalent primary Env antigen formulations were used, the DNA primeprotein boost approach was more effective than the monovalent primary Env antigen in eliciting rabbit NAbs against a wide range of selected primary viral isolates across subtypes A, B, C, D and E [27].…”
Section: Introductionsupporting
confidence: 81%
“…Serum and PBMC samples were collected at Study Weeks 0, 2,4,6,12,14,16,20,22,24,28,30,32,36 and 52 to measure antibody and CMI responses. All volunteers were recruited and enrolled in the Clinical Vaccine Research Unit, UMMS.…”
Section: 3b Study Design and Immunization Schedule-thismentioning
confidence: 99%
“…It is possible that immunizing with an immunogen with better CD4-binding properties would result in more potent VHH. Previous studies have shown that purified trimeric envelope proteins are somewhat better at eliciting cross-subtype-neutralizing antibodies than monomeric recombinant gp120 (6,7,22,32,38,90). We are currently screening llamas immunized with recombinant trimeric gp140.…”
Section: Discussionmentioning
confidence: 99%
“…SOSIP gp140 Preparation. JR-FL SOSIP gp140 trimers were produced according to published methods (30). For production of KNH1144 SOSIP gp140 trimers, 293 T cells were seeded into triple flasks (Corning Life Sciences) in DMEM with 10% fetal bovine serum and supplements 24 h prior to transfection.…”
Section: Methodsmentioning
confidence: 99%